2015
DOI: 10.1515/jaots-2015-0204
|View full text |Cite
|
Sign up to set email alerts
|

The Photocatalytic Performance of Benzene- Modified TiO2 Photocatalysts under UV-vis Light Irradiation

Abstract: Abstract:In this study a photocatalytic performance of new carbon-modified titanium dioxide photocatalysts was discussed. Benzene was used as carbon precursor. It was found that the photocatalytic activity of obtained samples increases with the increase of modification temperature and decrease of carbon concentration present in TiO 2 /C samples. This could be related to the kind of interactions between TiO 2 surface and carbon from thermal decomposition of benzene. The higher calcination temperature the less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…It was found that the material contains 0.96 wt.% of carbon what was reported in our previous paper [30]. Fig.…”
Section: Resultssupporting
confidence: 68%
“…It was found that the material contains 0.96 wt.% of carbon what was reported in our previous paper [30]. Fig.…”
Section: Resultssupporting
confidence: 68%
“…Anthracene (with a chemical purity >99%) purchased from Avantor Performance Materials Poland S.A. was used as carbon source. In our previous papers (7,9) benzene and naphthalene modification of TiO 2 was described. Mainly because of this reason the arene with three benzene rings was utilized as a carbon precursor.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…It was found that TiO 2 modification by non-metals such as carbon (3) causes light absorption in the visible region. For this purpose different inorganic and organic carbon precursors were used (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Wide range of used precursors make it possible to widen TiO 2 activation range of irradiation to visible region.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic process using TiO 2 as a photocatalyst is one of the most effective methods for degradation of organic contaminations such as: phenol [1–4], pesticides [5, 6], dyes [7–10], drugs [11] or bacteria and viruses [12, 13]. Photocatalysis is an economic method where pollutants are converted into simple chemicals such as carbon dioxide, water and non‐toxic mineral acids [14, 15].…”
Section: Introductionmentioning
confidence: 99%